Development of Tourism Objects and Increasing Tourist Visits at Burake Tourism Objects in Tana Toraja Regency - M. Awaluddin (Universitas Negeri Makassar, 2021)
Optimally developing tourism can increase economic growth, this is because tourism is a sector that is considered profitable for many parties, such as the government, society and the private sector. This study aims to determine the development of tourist objects and increase in tourist visits to Bureke. This research method is qualitative with a descriptive approach using primary and secondary data sources. Data collection is carried out through observation, interviews and documentation. The data analysis technique used a qualitative interactive model. The results of the study show that the development of tourist objects can increase tourist visits seen from tourist attractions where in tourist attractions there is the main attraction for tourists to come to visit, namely the statue of Jesus as the main object besides that there is also a statue of the Virgin Mary, a glass adrenaline bridge which is the only item in Toraja, photo spots and cool and beautiful natural scenery to attract tourist visits. Marketing and Promotion that attracts tourist visits. Transportation of income and desires based on research results there are many deficiencies, especially existing facilities that are not fully functioning optimally and also fees for entering and enjoying burake attractions are subject to tariffs based on.